2017
DOI: 10.5853/jos.2016.01655
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide “Hospital Emergent Capability Accreditation by Level-Stroke” Improves Stroke Treatment in Taiwan

Abstract: Background and Purpose Recombinant tissue plasminogen activator (rtPA) is one of the proven therapies that improve the outcome of patients with acute ischemic stroke (AIS). In 2009, the Ministry of Health and Welfare, Executive Yuan, Republic of China, launched the project “Hospital Emergent Capability Accreditation by Level-Stroke (HECAL-Stroke)” to improve AIS treatment in Taiwan. The current study was performed to determine whether the project launched by the government was effective in promoting rtPA thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 21 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…27 However, hospital admission rates for AIS in Lithuania in 2019 were still high despite an obvious downward trend from the highest stroke incidence worldwide in 2010. 2,28 Ample previous studies have shown a continuous increase in IV rtPA 26,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and EVT rates for AIS [46][47][48] in different countries over different study periods. However, our data show that Lithuania experienced a countrywide breakthrough of IV rtPA use only after the introduction of a comprehensive national policy.…”
Section: Discussionmentioning
confidence: 98%
“…27 However, hospital admission rates for AIS in Lithuania in 2019 were still high despite an obvious downward trend from the highest stroke incidence worldwide in 2010. 2,28 Ample previous studies have shown a continuous increase in IV rtPA 26,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and EVT rates for AIS [46][47][48] in different countries over different study periods. However, our data show that Lithuania experienced a countrywide breakthrough of IV rtPA use only after the introduction of a comprehensive national policy.…”
Section: Discussionmentioning
confidence: 98%
“…These efforts are primarily intended to enhance hyperacute care of patients with stroke, improve patients’ long-term prognosis through early comprehensive rehabilitation, and provide additional education programs for maintenance and secondary prevention. Therefore, these efforts are directly related to the acute phase survival rate 13 , 29 and can reduce chronic phase mortality and improve the long-term quality of life after stroke 30 . Model 1 showed no significant increase in the chronic phase mortality risk at the city or county level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on the trends in IV rt-PA use for acute ischemic stroke over specific time periods in various countries: 2003 to 2006, [ 25 ] 2003 to 2010, [ 26 ] and 2007 to 2010 [ 27 ] in Sweden; 2000 to 2012 [ 28 ] and 2003 to 2011 [ 29 , 30 ] in the US; 2007-2009 in Germany [ 31 ] ; 2005 to 2012 in the Netherlands [ 32 ] ; 2009 to 2014 in Taiwan [ 33 ] ; 2014 to 2018 in South Korea [ 34 ] ; and 2006 to 2018 in Austria. [ 35 ] These studies have observed continuous increases in IV rt-PA use over the study periods in their respective countries.…”
Section: Discussionmentioning
confidence: 99%